2010
DOI: 10.1542/peds.2009-1878c
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation, Diagnosis, and Treatment of Gastrointestinal Disorders in Individuals With ASDs: A Consensus Report

Abstract: Autism spectrum disorders (ASDs) are common and clinically heterogeneous neurodevelopmental disorders. Gastrointestinal disorders and associated symptoms are commonly reported in individuals with ASDs, but key issues such as the prevalence and best treatment of these conditions are incompletely understood. A central difficulty in recognizing and characterizing gastrointestinal dysfunction with ASDs is the communication difficulties experienced by many affected individuals. A multidisciplinary panel reviewed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
612
2
31

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 749 publications
(670 citation statements)
references
References 73 publications
25
612
2
31
Order By: Relevance
“…The current study population reported that 53.1% of the children with ASD experience gastrointestinal problems; other studies have found that the prevalence of gastrointestinal problems in children with ASD ranges from 9% to 70% or higher. 20 Additionally, the sex distribution among the children with ASD (78.4% male), the proportion of sleep problems (49.0%), the history of regression into ASD (61.9%), and the use of CAM (80.9%) were also similar to the findings from other studies. 1,14,19,21 Why do parents turn to CAM treatments for their children with ASD?…”
Section: Discussionsupporting
confidence: 82%
“…The current study population reported that 53.1% of the children with ASD experience gastrointestinal problems; other studies have found that the prevalence of gastrointestinal problems in children with ASD ranges from 9% to 70% or higher. 20 Additionally, the sex distribution among the children with ASD (78.4% male), the proportion of sleep problems (49.0%), the history of regression into ASD (61.9%), and the use of CAM (80.9%) were also similar to the findings from other studies. 1,14,19,21 Why do parents turn to CAM treatments for their children with ASD?…”
Section: Discussionsupporting
confidence: 82%
“…23 At the present time, the true prevalence of gastrointestinal (GI) disorders in ASD is largely unknown, with estimations ranging from 9% to 70% or higher. 24 Evidence-based guidelines for the evaluation of GI symptoms are not yet available for individuals with ASD. However, recently, 8 experienced gastroenterologists reviewed the current literature and published guidelines regarding GI symptoms that frequently occur in the general pediatric population.…”
Section: Gastrointestinal Disordersmentioning
confidence: 99%
“…In addition, these guidelines also raise awareness of the association of GI disorders with self-injurious behavior and sleep disturbances, and the frequent atypical presentation of GI dysfunction in individuals with ASD. 22,24 Although some ASD persons present with symptoms that are easily recognized by most healthcare providers, many others may not. As previously noted, atypical behaviors may include chest tapping, facial grimacing, and intermittent gulping, chewing on nonedible objects, including shirts and sleeves, constant eating or drinking, seeking of abdominal pressure, aggressions, and selfinjurious behaviors to name just a few.…”
Section: Gastrointestinal Disordersmentioning
confidence: 99%
“…After 78 years of age, head growth slows down to below normal; (iv) ASD is a systemic disorder, with many patients displaying macrosomy [55], gastrointestinal symptoms [11], and immune abnormalities [10,97];…”
Section: Conclusion: Clinical and Research Perspectivesmentioning
confidence: 99%
“…These anomalies would later result in reduced long-distance neuronal connectivity, yielding a "dysconnection syndrome" [5,6]. However, until recently it was believed that only specific brain regions were affected in autistic individuals, while increasing evidence shows that autism is a systemic disease involving not only the central nervous system (CNS), but also other organs, such as the gut, and the immune system [7][8][9][10][11].…”
mentioning
confidence: 99%